THE EFFECT OF PHYSICAL ACTIVITY ON THE BODY OF SCHOOLCHILDREN IN PHYSICAL EDUCATION LESSONS - Arabboev Kakhramon Tokhirzhonovich (Galaxy International Interdisciplinary Research Journal, 2023)
The article describes the influence of physical activity on the body of schoolchildren, and also considers the issues of taking into account the age, gender and physical fitness of students when performing physical activity. The author identifies internal and external indicators of physical activity.